Grab mobile application: a usability evaluation - Hussain, Azham; Mkpojiogu, Emmanuel O. C.; Jama Isse, Ahmed; Mohammed, Rabea Abdulrahman (IP Publishing LLC, 2018)
This study attempts to evaluate the mobile usability of a Car Grab application. This car Grab application is prominently used in South East Asia to assist commuters seeking for transportation services. The usability evaluation was carried out at Universiti Utara Malysia, UUM, using 20 student participants as users. The results of the evaluation show that the Grab mobile application was usable but with some usability issues observed.